Modulation of basophils' degranulation and allergy-related enzymes by monomeric and dimeric naphthoquinones. - Brígida R Pinho; Carla Sousa; Patrícia Valentão; Jorge M A Oliveira; Paula B Andrade (PLoS ONE)
Allergic disorders are characterized by an abnormal immune response towards non-infectious substances, being associated with life quality reduction and potential life-threatening reactions. The increasing prevalence of allergic disorders demands for new and effective anti-allergic treatments. Here we test the anti-allergic potential of monomeric (juglone, menadione, naphthazarin, plumbagin) and dimeric (diospyrin and diosquinone) naphthoquinones. Inhibition of RBL-2H3 rat basophils' degranulation by naphthoquinones was assessed using two complementary stimuli: IgE/antigen and calcium ionophore A23187. Additionally, we tested for the inhibition of leukotrienes production in IgE/antigen-stimulated cells, and studied hyaluronidase and lipoxidase inhibition by naphthoquinones in cell-free assays. Naphthazarin (0.1 µM) decreased degranulation induced by IgE/antigen but not A23187, suggesting a mechanism upstream of the calcium increase, unlike diospyrin (10 µM) that reduced degranulation in A23187-stimulated cells. Naphthoquinones were weak hyaluronidase inhibitors, but all inhibited soybean lipoxidase with the most lipophilic diospyrin, diosquinone and menadione being the most potent, thus suggesting a mechanism of competition with natural lipophilic substrates. Menadione was the only naphthoquinone reducing leukotriene C4 production, with a maximal effect at 5 µM. This work expands the current knowledge on the biological properties of naphthoquinones, highlighting naphthazarin, diospyrin and menadione as potential lead compounds for structural modification in the process of improving and developing novel anti-allergic drugs.